Enablers and Barriers of COVID-19 Vaccination in the Philippines - Evalyn Roxas; Paulyn Jean Acacio-Claro; Maria Margarita Lota; Alvin Abeleda; Soledad Natalia Dalisay; Madilene Landicho; Yoshiki Fujimori; Jan Zarlyn Rosuello; Jessica Kaufman; Margaret Danchin; Vicente Belizario; Florian Vogt (Vaccines, 2025)
Background: The COVID-19 pandemic prompted extensive vaccination efforts globally, yet in the Philippines, many families remained unvaccinated. Caregivers are key decision-makers for family vaccination, but evidence on factors influencing their own vaccine uptake is limited. Methods: A cross-sectional survey of primary caregivers was conducted in low COVID-19 vaccine uptake regions in the Philippines from July to October 2023 using a validated questionnaire. Multivariable logistic regression identified enablers and barriers to vaccine uptake. Results: Among 775 respondents, 72.3% completed primary vaccination, 3.3% had incomplete vaccination, and 24.4% were unvaccinated. Key factors for vaccination included self, family, and community protection, and the influence of government regulations. Distrust in vaccine safety was the main barrier. Positive associations with vaccine uptake were found for age [30–45 years (aOR = 2.23) and 46–59 years (aOR = 2.84)], education [secondary (aOR = 2.25) and tertiary (aOR = 4.93)], and employment (aOR = 1.99). Confidence in vaccine safety (aOR = 1.92), vaccine effectiveness (aOR = 2.23), and satisfaction with vaccination efforts (aOR = 2.39) were additional enablers. Disagreement with restrictions on the unvaccinated was a barrier (aOR = 0.31). Conclusions: This study identified multiple factors influencing COVID-19 vaccination among primary caregivers in low uptake areas of the Philippines. Interventions addressing perceptions about vaccine safety and effectiveness, particularly among younger and less educated caregivers, may improve public trust and satisfaction with vaccination efforts.